Analysis of KBL 02 Feeder Protection Coordination to Improve Reliability at PT PLN (Persero) Djty ULP Purwokerto City - Nia Rohchani; Hamdani Hamdani; Reza Juliangga (Jurnal Info Sains : Informatika dan Sains, 2026)
In 2017, the KBL02 feeder was recorded as having a low reliability level due to the high frequency of PMT and recloser tripping faults. Based on the fault data evaluation, most fault locations were downstream of the recloser, but the protection system actually caused the outgoing PMT to operate first. This condition resulted in a wider outage area and reduced electricity supply to customers, resulting in an increase in the SAIDI and SAIFI reliability index values ​​at PT PLN (Persero) Purwokerto City ULP. The main problem was caused by inconsistencies in protection coordination between the outgoing PMT and the KBL02.067 recloser, which was influenced by recloser placement that was not aligned with the OCR and GFR settings. This study aims to evaluate protection coordination and determine recloser relocation based on fault current calculations and protection settings. The results are expected to improve protection system selectivity and enhance power distribution reliability at the KBL02 feeder.